BIMBINGAN DAN PENYULUHAN TENTANG PENTINGNYA KUALITAS PELAYANAN PADA USAHA JASA DI LINGKUNGAN RW.VII, DESA SUDIMORO,KEC.MOJOLANGU KEL.LOWOKWARO KOTA MALANG - Helmy Adi Saksana (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2016)
The purpose of Community Service is to find an appropriate alternative guidance and counseling, through: a. Increase knowledge and the ability of the Entrepreneur in the field of operations, especially the field of practical servicing quality. b. Increase application of education and training results in the framework of science and technology development. c. Creating opportunities for employment opportunities in the economic activities of the community in the form of increased income .d. Establish closer relationships between the Politeknik Negeri Malang with Service Entrepreneurs. With this devotion is expected that entrepreneurs are able to provide quality service, this will affect thd: a. Straightforward tariff / pricing.b.Increase of the main source of income of the entrepreneur.c. Services easily known to customers or prospective customers. Creating wider employment opportunities. Enterprises can be developed.From the preliminary survey it is found that the problem is then solved by: a.To give lecture on the importance of service quality.b. provide guidance and practice about the right service quality. c.Discussion / question and answer, which is associated with the existing problems.Some of the results of this Service are: -This devotion is an activity and knowledge and application which is very important in order effort to get additional skill for Service Business. -The participant's motivation is very high, it is seen from the enthusiasm of the participants follow to the end of the program. -That the average acceptance of the material delivered by the instructor is good enough.